BE_VERWALTUNGSGERICHT 100 2024 86 vom 20. Februar 2024 - BE Verwaltungsgericht (2024)
Schenkungssteuer 2018 (Entscheid der Steuerrekurskommission des Kantons Bern vom 20. Februar 2024; 100 23 59) | Erbschaft/Schenkung